Pengaruh Promosi, Aksesibilitas, dan Word of Mouth Destinasi Wisata dalam Meningkatkan Kunjungan Wisatawan di Obyek Wisata Atauro, Dili - Dos Santos, Veonita Amena; Luh Komang Candra Dewi; I Nengah Subadra (CV. ULIL ALBAB CORP, 2025)
This study aims to analyze the influence of promotion, accessibility, and tourism destination attractiveness on tourist visits to Atauro Island, Dili. Atauro is recognized as one of the leading ecotourism destinations in Timor-Leste, offering unique natural, cultural, and marine biodiversity attractions. However, tourist arrival data still shows significant fluctuations each year. This research employed a quantitative approach by distributing questionnaires to tourists as respondents. The data were analyzed using multiple linear regression to examine both partial and simultaneous effects of the variables. The results reveal that promotion, accessibility, and destination attractiveness have a positive and significant impact on tourist visits, both individually and collectively. These findings highlight the importance of effective promotional strategies, improved accessibility, and sustainable destination management to enhance Atauro’s competitiveness as an international tourist destination.